Restoring Trusts without Losing Face: An Episode in the History of China â Indonesia Relationship - Muas, Tuty Enoch (ASPENSI in Bandung, Indonesia, 2015)
ABSTRACT: The main factor of the frozen China â Indonesia diplomatic relationship was the loss of trusts of Indonesia toward China in connection with the G-30-S (Gerakan 30 September or 30th September Movement) in 1965. Interestingly, in this frozen diplomatic relationship era, there was a direct trade agreement between CCPIT (China Council for Promotion on International Trade) and KADIN (Kamar Dagang dan Industri Indonesia or Indonesia Chamber of Commerce and Industry). This fact leads to the question: is there and what are the real efforts of China to restore the trust from Indonesia? This research used the history research method and enhanced by the âMianziâ concept. The result of this research shows that since PRC (People Republic of China) stipulate revolutionary diplomatic line, which makes China closer to the USA (United States of America), its relationship with the neighboring countries, especially those tied in the ASEAN (Association of South East Asia Nations) organization, is getting better. This improvement can be seen as a way to gain the trust from Indonesia again. It is also clearly seen that China uses the third party and makes the advantages of the opportunities given by the internal and external development to create a good image to Indonesia. All these steps have led the respect factors in the âMianziâ concepts has showed very meaningful influences within the process. Although the CCPIT â KADIN agreement is not the mostly expected result, but it is the important moment for the growing trust of these two countries and the effort to normalize the China â Indonesia diplomatic relationship.Â Â KEY WORDS: China-Indonesia relationship, trust, respect factors, âMianziâ concept, third party, effort to normalize, and diplomatic relationship.Â Â About the Author: Dr. Tuty Enoch Muas is a Senior Lecturer at the Chinese Studies Program, Faculty of Humanities UI (University of Indonesia), UI Campus Depok, West Java, Indonesia. For academic interests, the author can be contacted via e-mail at: mutu1722@yahoo.comHow to cite this article? Muas, Tuty Enoch. (2015). âRestoring Trusts without Losing Face: An Episode in the History of China â Indonesia Relationshipâ in TAWARIKH: International Journal for Historical Studies, Vol.6(2) April, pp.223-236. Bandung, Indonesia: Minda Masagi Press and UNHAS Makassar, ISSN 2085-0980. Chronicle of the article: Accepted (January 29, 2014); Revised (July 29, 2014); and Published (April 28, 2015).